Fabrications and Properties of Heteroatom-Based Co-Doped Biochar for Environmental Application: A Review - Meizhi Yang; Suxing Luo; Ping Zeng; Yuanhui Wu (Separations)
For the past few years, biochar has emerged as a promising material for the removal of various pollutants from aquatic environments, owing to its advantageous characteristics, such as tunable porosity, abundant surface functional groups, ease of modification, and relative stability. Co-doping biochar with heteroatoms significantly enhances its surface properties by introducing additional functional groups and surface defects, which facilitate the adsorption and catalytic degradation of pollutants. This review conducts bibliometric analyses of relevant publications, synthesis methodologies, applications, and reaction mechanisms of co-doped biochar as an adsorbent and catalyst for contaminant removal, due to the synergistic effects of doping elements and biochar features. Furthermore, co-doping strategies and associated properties including specific surface area (SSA), surface functional groups, and defects of biochar are analyzed. Finally, future research directions are proposed to improve the efficiency of biochar in water and soil remediation applications. In summary, this review advances the frontier of research on heteroatom-based co-doped biochar and offers new insights into strategies for effective contaminant removal.